2015
DOI: 10.5430/ijfr.v7n1p109
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Total Production and Public Spending in Mexico: Keynes versus Wagner

Abstract: This paper studies the relationship between public spending and production in Mexico. It aims to assess the direction of causality between these two variables ranging from economic growth to public expenditure (Wagner hypothesis) or public spending to economic growth (Keynesian hypothesis). Annual time series for the period 1925-2014 of production and public spending in real terms (1970 based) and logarithms were used. The test method involved three steps: 1) unit root tests; 2) cointegration test of Engle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…On the other hand, Cavicchioli and Pistoresi (2016) and Afonso and Alves (2017) provide support for Wagner's Law in the case of developed economy. Several other studies that are in line with these findings include studies in developing countries by Ifa and Guetat (2018), for the case of Tunisia and Morocco, Kurniawati (2018) for the case of Indonesia and Sanchez-Juarez et al (2016) in the case of Mexico. In addition, the study in more developed countries by Magazzino (2010) in western part or Europe confirms the validity of the Keynesian hypothesis, in line with Wang et al (2016) for the case of eastern part of Europe.…”
Section: Resultssupporting
confidence: 59%
“…On the other hand, Cavicchioli and Pistoresi (2016) and Afonso and Alves (2017) provide support for Wagner's Law in the case of developed economy. Several other studies that are in line with these findings include studies in developing countries by Ifa and Guetat (2018), for the case of Tunisia and Morocco, Kurniawati (2018) for the case of Indonesia and Sanchez-Juarez et al (2016) in the case of Mexico. In addition, the study in more developed countries by Magazzino (2010) in western part or Europe confirms the validity of the Keynesian hypothesis, in line with Wang et al (2016) for the case of eastern part of Europe.…”
Section: Resultssupporting
confidence: 59%
“…However, there is an inverse impact of economic growth on external debt. The investigation of Sánchez-Juárez and García-Almada [48] has revealed that public debt is positively correlated with public investment and that this generates economic growth. Kamran and Ahmed [49] evaluated the impact of military spending on external debt in highly indebted and low-income developing countries, such as India, Pakistan, Brazil, and the Philippines for the period between 1988 and 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Next, Keynes' theory is valid, as found in the studies of Babatunde [16], Ebaidalla [17], Karahan and C ¸olak [5], Pula and Elshani [18], Sanchez-Juarez et al [19], and Wang et al [20]. For instance, a study carried out by Ebaidalla [17] in Sudan from 1970 to 2008 found that only GE has a Granger causality to GDP in the short run.…”
Section: Literature Reviewmentioning
confidence: 87%